Comparing traceability through information retrieval, commits, interaction logs, and tags - Seiler, Marcus; Hübner, Paul; Paech, Barbara (IEEE Xplore digital library, 2019)
Traceability is used to follow and understand the relationships between various software engineering artifacts such as requirements and source code. Comprehensive traceability of software engineering artifacts is important to ensure that a software can be further developed or maintained. Traceability links are often created manually by using commit ids or retrospectively by using information retrieval (IR). However, creating traceability links manually is costly and it is error-prone in retrospect. As part of our ongoing research on feature management where traceability is also of interest, we use a lightweight tagging approach to relate artifacts. We want to investigate how such a tag-based approach compares to approaches using commit ids, interaction logs (IL), and IR for creating traceability links.